2023
DOI: 10.1002/alz.13074
|View full text |Cite
|
Sign up to set email alerts
|

Preserved autophagy in cognitively intact non‐demented individuals with Alzheimer's neuropathology

Abstract: INTRODUCTIONGrowing evidence supports that dysfunctional autophagy, the major cell mechanism responsible for removing protein aggregates and a route of clearance for Tau in healthy neurons, is a major finding in demented Alzheimer's disease (AD) patients. However, the association of autophagy with maintenance of cognitive integrity in resilient individuals who have AD neuropathology but remain non‐demented (NDAN) has not been evaluated.METHODSUsing post mortem brain samples from age‐matched healthy control, AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…At lower Aβ levels, there are higher levels of many proteins associated with protein degradation and autophagy, including CTSD, 41,42 GPNMB, 43,44 HSC70, 45–47 and Park5, 48,49 whereas only LAMP2A 47 displays higher expression levels with increasing Aβ (Figure 7). Similarly, NFT‐bearing neurons in definite PART have higher levels of ATG5 50,51 in CA1 and entorhinal and higher GBA in CA2 compared to ADNC and possible PART, while non‐NFT‐bearing neurons in definite PART have higher ATG5 in CA2 and entorhinal, higher CTSD in CA2, and higher HSC70 in entorhinal compared to ADNC and possible PART (Figures 4 and 6). This suggests that these proteins involved in proteostasis may be assisting in regulating the levels of aggregated proteins, including Aβ in these cases.…”
Section: Discussionmentioning
confidence: 92%
“…At lower Aβ levels, there are higher levels of many proteins associated with protein degradation and autophagy, including CTSD, 41,42 GPNMB, 43,44 HSC70, 45–47 and Park5, 48,49 whereas only LAMP2A 47 displays higher expression levels with increasing Aβ (Figure 7). Similarly, NFT‐bearing neurons in definite PART have higher levels of ATG5 50,51 in CA1 and entorhinal and higher GBA in CA2 compared to ADNC and possible PART, while non‐NFT‐bearing neurons in definite PART have higher ATG5 in CA2 and entorhinal, higher CTSD in CA2, and higher HSC70 in entorhinal compared to ADNC and possible PART (Figures 4 and 6). This suggests that these proteins involved in proteostasis may be assisting in regulating the levels of aggregated proteins, including Aβ in these cases.…”
Section: Discussionmentioning
confidence: 92%
“…In light of our recent study revealing reduced autophagy in AD and preserved in NDAN individuals, we hypothesize that enlargement of the dendritic diameters may indicate a stressed autophagic process, resulting in the accumulation of partially digested cellular matter due to disrupted autophagosome‐lysosome fusion. 20 NDAN subjects exhibit an increase of spine density in regions distant from plaques compared to both AD patients and CTRL individuals. This suggests the existence of potential compensatory mechanisms that counter dendritic loss near Aβ plaques, unlike in AD, where such mechanisms are absent.…”
Section: Discussionmentioning
confidence: 87%
“… 12 , 16 Those studies emphasize the importance of further investigating dendritic structures in these subjects to deepen our understanding of cognitive resilience mechanisms in AD. We previously reported that synapses of NDAN subjects displayed a unique proteomic profile and miRNA regulation, 17 and NDAN individuals have an increased number of neural stem cells in the hippocampus, 18 preserved antioxidant, 19 and autophagy response, 20 and their synapses are resistant to the detrimental binding of Aβ and tau oligomers. 21 , 22 Although NDAN and AD subjects exhibit comparable levels of pathological Aβ plaque deposition, NDAN individuals appear to be resistant to the well‐documented effects of amyloid deposits on dendrites and axons, which typically lead to spine loss, dendritic atrophy, and axonal varicosities, culminating in widespread and permanent neural disruption.…”
Section: Introductionmentioning
confidence: 99%
“…Unraveling the intricacies of AD etiopathogenesis is an arduous but not insurmountable task that has been approached in multiple ways, as illustrated in this review. However, to find the breakthrough that is so urgently needed, the evidence supports a move away from simplistic attempts to lower amyloid or tau production and perhaps to move on to a more complex strategy that preserves neuron longevity, modulates autophagy, and maintains mitochondrial integrity and bioenergetic functions [ 357 , 358 ].…”
Section: The Futurementioning
confidence: 99%